Latent Autoimmune Diabetes of Adults Due to Positive Zinc Transporter 8 Antibody - Jacob Maniattu; Mc Anto Antony; Siddharth Patel; Alvin Maliakal (Annals of Internal Medicine: Clinical Cases)
This case series reports 3 patients who were diagnosed with type 2 diabetes mellitus (T2DM), treated with oral antidiabetic medications, referred to our endocrinology clinic due to poor glycemic control, and were diagnosed with latent autoimmune diabetes of adults due to the isolated presence of ZnT8 antibody. Our cases highlight a few important learning points, such as maintaining a high degree of suspicion for the development of autoimmunity in a patient with T2DM with progressive or rapid worsening in glycemic control and the need to include the ZnT8 antibody in the panel of other diabetes antibodies during the work-up for autoimmune DM.